The analysis of apricot and sweet cherry pollen viability after cryopreservation - M. N. Sitnikov; V. G. Verzhuk; A. V. Pavlov; D. D. Bondaruk (Труды по прикладной ботанике, генетике и селекции)
Cryopreservation minimizes the risk of losing valuable accessions and reduces the material costs of plant resources maintenance. By using the method of pollen long-term storage in cryobanks, it is possible to keep pollen grains viable for an unlimited time. In the course of the research, cryoconservation of pollen of stone fruit crops was performed and pollen viability was checked after exposure to ultra-low temperatures (-196°С) under laboratory conditions. The studies were carried out on apricot (Armeniaca vulgaris Lam.) and sweet cherry (Cerasus avium (L.) Moench) plants, from which pollen was collected. Evaluation of viability in laboratory conditions was carried out by germination on various nutrient media. The possibility of long-term pollen preservation in liquid nitrogen vapor is shown. Based on the results obtained, a collection of pollen is being created for implementing various breeding programs.